Himpunan Perundang-Undangan Pertanahan Dan Petunjuk PPAT Di Indonesia Jilid 1-2 - [Tidak Terdaftar] (CV. Citra Mandiri, 2004)
Himpunan Perundang-Undangan Pertanahan Dan Petunjuk PPAT Di Indonesia Jilid 1-2